2009
DOI: 10.1002/clc.20662
|View full text |Cite
|
Sign up to set email alerts
|

Quartiles of Peak Troponin Are Associated with Long‐term Risk of Death in Type 1 and STEMI, but Not in Type 2 or NSTEMI Patients

Abstract: Background: The prognostic value of peak cardiac troponin (cTn) in different types of acute myocardial infarction (AMI) under the universal clinical classification is unknown. Hypothesis: We tested the hypothesis that the prognostic value of cTn varies with its peak level and type of AMI. Methods: We studied 345 consecutive patients with AMI with mean follow-up of 30.6 months according to quartiles of peak cTn level (QPTL) and the type of AMI. The study outcomes were the major adverse cardiovascular events (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…As this was a single-center study including a small sample size and event rate in contrast to the complex Cox regression equation used, there may have been many potential confounding factors that could account for the results conflicting with those of previous reports [18,19,20]. Notwithstanding, the study sheds an important light on an old-fashioned but certainly important issue: the importance of examining cTn levels even hours or days after diagnosis as a tool to further risk-stratify NSTEMI patients far beyond the initial diagnostic protocols, which are, controversially, getting progressively faster.…”
contrasting
confidence: 55%
“…As this was a single-center study including a small sample size and event rate in contrast to the complex Cox regression equation used, there may have been many potential confounding factors that could account for the results conflicting with those of previous reports [18,19,20]. Notwithstanding, the study sheds an important light on an old-fashioned but certainly important issue: the importance of examining cTn levels even hours or days after diagnosis as a tool to further risk-stratify NSTEMI patients far beyond the initial diagnostic protocols, which are, controversially, getting progressively faster.…”
contrasting
confidence: 55%
“…One of the studies originally identified by our search criteria was excluded from pooled analysis because no indication was provided about the type of cardiac troponin that was measured [22]. However, the results deserve a brief mention.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to the transmural myocardial injury that occurs in the setting of STEMI. 19 Patients with STEMI have a persistent and complete occlusion of an epicardial artery putting a large myocardial territory at risk of ischemia. 4 In contrast, NSTEMI and UA results from varying degree of coronary obstruction, but without a complete occlusion of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The Siemens Immulite 1000 (Erlangen, Germany) troponin I (99th percentile: 0.19 µg/L, CV at 99th percentile: 11, CV at 10th percentile: 0.22, with reference range being 0.01-0. 19) and Siemens ADVIA Centaur BNP (reference < 100 ng/L) assays were used. The daily use of aspirin, statin, β-blockers, calcium channel blockers, and angiotensin converting enzyme inhibitors (ACE-I) or angiotensin receptor blockers (ARB) previous to hospitalization was noted for each patient.…”
Section: Methodsmentioning
confidence: 99%